Compact and efficient WPT systems using half-ring resonators (HRRs) for powering electronic devices. Issue 2 (8th October 2018) - Atallah, Hany A.
Abstract : This work presents a novel efficient and compact size coupled resonator system for wireless power transfer (WPT) based on compact half-ring resonators defected ground structure (HRRs-DGS). The proposed design is capable of supplying low power electronic devices. The suggested system is based on coupled resonators of DGS. An HRR-DGS band-stop filter is designed and proposed, and when two HRRs-DGS are coupled back-to-back, it transfers to a band-pass filter leading to a compact and highly efficient WPT system working at 3.4 GHz. The measured efficiency of the proposed coupled HRRs-DGS system is around 94% at a transmission distance of 12 mm which is filled with foam for stable measurements. The proposed design is suitable for charging electronic devices such as wireless sensor nodes at 3.4 GHz. Simulation and experimental results have shown acceptable agreement.